VARIABILITA DEL BRACHIDIO Dl GRYPHUS MINOR (PHILIPPI) TEREBRATULIDA, BRACHIOPODA (Rivista italiana di Paleontologia e Stratigrafia, 2020)
A sample of 104 specimens of Gryphus minor (Philippi), collected in a single bed in Lower Pleistocene clays of Croce Valanidi (Reggio Calabria, Italy) is here considered. The variation of the brachidium was studied by means of 11 characters. Length and width of the brachial valve were also measured. Basic statistics were carried out on these data, as well on the comparisons between characters.Results indicate a wide range of variation for most of the characters of the brachidium, and a positive correlation between length and width of the brachial valve, length and width of the brachidium.Other correlations between general outline of the valve and brachidium characters are scanty. Hints from this study to the Terebratulid taxonorny seem to suggest that, due to the Wide range of variation of the brachidium, the use of few specimens to discriminate between nearby species could result unsatisfactory